Tax Policy and the Environment : Theory and Practice - Nellor, David (IMF Working Papers; Working Paper ;, 1994)
This paper provides a framework for examining environment taxes. It reviews the theoretical efficiency of three types of environment taxes: taxes on emissions or Pigouvian taxes; taxes on productive inputs or consumer goods whose use is related to environmental damage; and environment-related provisions in other taxes. A survey of environment taxes in 42 countries--drawn from developing countries, economies in transition, and industrial countries--illustrates that the use of environment taxes differs dramatically from the recommendations of environment tax theory. This divergence between the theory and practice of environment taxes can be attributed to several factors; environment taxes are difficult to implement, there are many factors that impede their effectiveness, and their introduction may be discouraged by their implications for other policy objectives.